2012
DOI: 10.1155/2012/515901
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Isolated from KoreaCitrus aurantiumL. Induce G2/M Phase Arrest and Apoptosis in Human Gastric Cancer AGS Cells

Abstract: Aim of the Study. Citrus species is used in traditional medicine as medicinal herb in several Asian countries including Korea. Flavonioids became known as various properties, such as anti-oxidants, anti-inflammation and anti-cancer, and so forth. The present study, the anti-cancer effect of flavonioids isolated from Citrus aurantium L. in human gastric cancer AGS cells has been investigated. Materials and Methods. The anti-proliferative activity was assayed using MTT assay. Cell cycle analysis was done using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 39 publications
3
44
1
Order By: Relevance
“…In our previous studies we have shown high content of hesperidin in C. aurantium [16]. In food industry Citrus fruits are mainly used as fresh juice and Citrus based juice.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In our previous studies we have shown high content of hesperidin in C. aurantium [16]. In food industry Citrus fruits are mainly used as fresh juice and Citrus based juice.…”
Section: Discussionmentioning
confidence: 92%
“…Natural products are considered to be safe and also reduce the mutagenicity in normal cells [19]. In our previous studies we have also reported Citrus aurantium extracts, Scutellaria baccalensis extracts and polyphenolic extracts of Lonicera japonica to possess anticancer activity in human gastric cancer, lung cancer and liver cancer cells respectively [16], [26], [27].…”
Section: Introductionmentioning
confidence: 95%
“…CAL consists of many flavonoids, naringin, hesperidin, poncirin, isosiennsetin, hexamethoxyflavone, sineesytin, hexamethoxyflavone, tetramrthnl-o-isoscutellaeein, nobiletin, heptamethoxyflavone, 3-hydoxynobiletin, tangeretin, hydroxypentamethoxyflavone, and hexamethoxyflavone [22,23]. …”
Section: Methodsmentioning
confidence: 99%
“…With the effect on circulating qi, drying dampness and transforming phlegm, it is used to treat cough and cancer in TCM practice. Current studies have indicated that the extracts or constituents of C. reticulata Blanco have anticancer effects on several tumor cell lines (Silalahi, 2002;Arias and Ramon-Laca, 2005), and its mechanism involving induction of apoptosis was demonstrated on human leukemic HL-60 (Hirano et al, 1995), gastric cancer (Kim et al, 2005;Lee et al, 2012b), colorectal cancer (Zheng et al, 2002), and lung cancer cells (Xiao et al, 2009). It is believed that the main active ingredients of C. reticulata Blanco are flavonoids, particularly polymethoxyflavones (PMFs), which are reported to have a role in inducing an increased level of intracellular Ca 2 þ and thus activating Ca 2 þ -dependent apoptotic proteases, and modulating key signaling proteins related to cell proliferation and apoptosis (Sergeev et al, 2007;Qiu et al, 2010).…”
Section: Apoptosis-inducing and Anti-proliferative Effectsmentioning
confidence: 99%